Roles of fairness in the relationship between performance evaluation systems and budget gaming behavior - SeTin, SeTin; Sembel, Roy; Augustine, Yvonne; Purwanti, Ari (Penerbit Universiti Kebangsaan Malaysia, 2021)
Budgetgaming is still an unsolved problem and requires a serious handling.The purpose ofthisstudyis to investigateif theperceptions of procedural fairness mediate the relationships between performance evaluation systems and budgetgamingbehavior. The surveywasconducted ongopublic manufacturing companiesinIndonesia with a division manager as a unit ofanalysis. A total of128 samples were analyzed using Partial Least Square WarpPLS 3.0. Theresults show that procedural fairness significantly mediates the relation between non-financial measure and budgetgaming. However,proceduralfairness does not mediate therelationshipbetween relative performance evaluation andbudget gaming.This study supports goal setting theory, agency theory,and organizational justice theorywhich providepractical implications in terms of overcoming budget gaming through the use of non-financial performance measures.